1979
DOI: 10.1002/eji.1830090313
|View full text |Cite
|
Sign up to set email alerts
|

T cell‐produced immunoglobulin binding factor (IBF) bears determinants coded for by the I region of the major histocompatibility complex and lacks allogeneic restriction

Abstract: An immunoglobulin binding factor (IBF) produced by in vivo alloantigen-activated T cells suppresses in vitro antibody production to sheep red blood cells (SRBC) and probably represents the soluble form of the T cell Fc receptor. To study the relationship between IBF and the major histocompatibility complex (MHC), two types of experiments were undertaken. First, different IBF were prepared by injecting thymocytes from mice of H-2k, H-2b and H-2d haplotypes into irradiated, allogeneic recipient mice. Cells recov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1980
1980
1987
1987

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 37 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…The effects observed with FcyR in cultures of human PBL are quite similar to those of murine IBF which suppresses primary antibody response and polyclonal activation by lipopolysaccharide without affecting the proliferative response [13], and mouse IBF itself was recently reported to inhibit the late stages of maturation of human B cells in the presence of P W or NOC extracts [14]. Alike those of IBF [15], the suppressive effects of human soluble FcyR are not restricted to syngeneic B cells.…”
Section: Discussionmentioning
confidence: 63%
“…The effects observed with FcyR in cultures of human PBL are quite similar to those of murine IBF which suppresses primary antibody response and polyclonal activation by lipopolysaccharide without affecting the proliferative response [13], and mouse IBF itself was recently reported to inhibit the late stages of maturation of human B cells in the presence of P W or NOC extracts [14]. Alike those of IBF [15], the suppressive effects of human soluble FcyR are not restricted to syngeneic B cells.…”
Section: Discussionmentioning
confidence: 63%
“…Suemura et al (23) reported that an IgE-specific suppressive factor ("IgE-TsF") was absorbed by an alloantiserum specific for determinants of the (KABJE)d region (23). IgG-BF derived from H-2k and H-2d mouse T cells and an H-2k T-cell hybridoma were absorbed by anti-Ia antisera specific for the appropriate la haplotype (24,25). However, the 8.3 IgE-BF sequence shares no homology with class II gene products (10), and genes encoding rodent IgE-BF are members of a multigene family that is not related to genes of the major histocompatibility complex (12).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the results presented here, studies currently being conducted in collaboration with W. H. Fridman and colleagues have shown that both hybridomas 27 and 34 express Fc receptors (FcR) specific for immunoglobulins of the IgG class (FcRy) (W. H. Fridman, et al Manuscript in preparation.). Moreover, like a T cell hybridoma constructed by these same investigators that is also FcRy positive (33), both hybridoma 27 and 34 secrete immunoglobulin-binding factor (IBF) activity (35)(36)(37), and their line (designated T2D4) appears to secrete AEF-like enhancing activity. It should be emphasized, however, that preferential expression of either AEF-enhancing or IBF-suppressive activities by the T2D4 and our hybridoma lines depends critically on the culture conditions used for the preparation of the biologically active supernates.…”
Section: Discussionmentioning
confidence: 99%